Spyramicine and Trimethoprim-Sulfamethoxazole Combination to Prevent Mother-To-Fetus Transmission of Toxoplasma gondii Infection in Pregnant Women: A 28-Years Single-center Experience. Issue 5 (14th February 2022) - Buonsenso, Danilo; Pata, Davide; Turriziani Colonna, Arianna; Iademarco, Mariella; De Santis, Marco; Masini, Lucia; Conti, Guido; Molle, Fernando; Baldascino, Antonio; Acampora, Anna; Luciano, Rita; Gallini, Francesca; et al.
Abstract : Background: There is weak evidence on the best treatment of pregnant women with Toxoplasma gondii infection to prevent the vertical transmission to the fetus. Methods: We conducted a 28-year retrospective study aiming to compare the efficacy of three therapeutic regimens [Spiramicyn alone (Spy) vs. Pyrimethamine-Sulfadiazine (P/S) vs. Spiramicyn with Trimethoprim-Sulfamethoxazole (Spy+TMP-SMX)] for the prevention of mother-to-fetus transmission of T. gondii infection. Results: 170 women were included: 58 (34.1%) had certain congenital toxoplasmosis (CT), 61 (35.9%) a probable infection and 41 (24.1%) possible infection. In total 97 mothers (57.1%) were treated with the Spy+TMP-SMX combination, 64 mothers (37.6%) were treated with Spy only and 8 mothers (4.7%) with P/S. Infected infants were 20/170 (11.7%). However, 8.2% (8/97) of infants born to mothers treated with Spy+TMP-SMX were infected, 20% (11/55) of infants born to women treated with Spy and 12.5% (1/8) of infants born to mothers treated with P/S were infected. Logistic regression analysis demonstrated that Spy treatment alone was associated with an increased risk of CT compared to the Spy+TMP-SMX combination (OR, 2.78, 95% CI 1.04-7.41, P value 0.041). No difference was observed when the Spy+TMP-SMX was compared with the P/S combination (OR 1.59; 95% CI 0.17 - 14.58; P value 0.682). Results were confirmed when the analyses were corrected by trimester of infection and by type of maternal treatment (OR 7.72; 95% CI 3.40-17.53, P value <0.001). Conclusions: The combination of Spy+TMP-SMX may be more effective in reducing the risk of maternal-fetal transmission of Toxoplasmosis compared to Spy alone; furthermore, this combination is not inferior to P/S, the current international standard-of-care maternal treatment for the prevention of CT. A prospective trial comparing the combination Spy+TMP-SMX with P/S would be necessary to provide definitive evidence on the best regimen for pregnant women with T. gondii infection.